Association between estimation of pulse wave velocity and all-cause mortality in critically ill patients with non-traumatic subarachnoid hemorrhage: an analysis based on the MIMIC-IV database - Li, Jianquan; Zhang, Meimei; Ye, Baning; Lu, Mingjie; Liao, Gang (Frontiers in Neurology, 2024)
Estimated pulse wave velocity (ePWV), which measures vascular aging, is an independent predictor of cardiovascular death. Nevertheless, the relationship between ePWV and all-cause mortality among patients suffering from non-traumatic subarachnoid hemorrhages (NSAH) remains obscure. Consequently, the objective of this study is to ascertain whether ePWV exerts influence on the prognosis of individuals afflicted with NSAH.Through the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, 644 eligible participants were included.The Kaplan-Meier survival curve method was employed to assess the disparity in survival status between the low and high ePWV cohorts.The Cox proportional hazard model was employed to investigate the association between ePWV and inpatient mortality among critically ill patients diagnosed with NSAH.The Restricted Cubic Spline (RCS) model was employed to examine the dose-response correlation.Subsequently, multivariate Cox regression analysis was performed to identify independent prognostic factors.Lastly, the impact of ePWV on inpatient mortality across various subgroups was evaluated through stratified analysis.Participants were categorized into two groups, delineated by their ePWV levels: a low ePWV level group and a high ePWV level group. Survival analysis unveiled that individuals with high ePWV exhibited a diminished survival rate compared to their counterparts with low ePWV. Following adjustment, low ePWV was significantly linked with a reduced risk of inpatient mortality among patients with NSAH (HR = 0.54, 95% CI = 0.32 -0.89, p = 0.016). Simultaneously, analysis employing the RCS model further substantiated a linear escalation in the risk of inpatient mortality with increasing ePWV values. Conclusions: Elevated ePWV levels have been identified as an independent risk factor for the rise in inpatient mortality among NSAH patients and as a significant predictor of the clinical outcome of NSAH.